Health consultations at a performing arts health centre among classical music students based on electronic health record data: a cross-sectional study - Steemers, Suze; van Rijn, Rogier M.; van Middelkoop, Marienke; Bierma-Zeinstra, Sita M. A.; Stubbe, Janine H. (Frontiers in Psychology, 2024)
Physical and mental health problems in music students are usually identified using self-reported data. The use of an Electronic Health Record database can avoid biases to give an overview of the extent of health problems in this population. Therefore, the aim of this study is to gain insight into both physical and mental health related issues in classical music students using this type of data collection. An Electronic Health Record database including five years of data from a Performing Arts Health Centre (PAHC) of a university or the arts, was used to analyze the number and characteristics of health consultations in music students. The total number of students, health consultations and the average number of visits per health consultation were calculated over five years. Furthermore, numbers and percentages of both physical and mental health consultations were registered. Also, the number and percentage of health consultations per instrument group were compared to the proportion of each instrument group within the specific sample. Over a period of five years, 230 students visited the PAHC and 417 health consultations were reported. 43.5% of the students who visited a health professional indicated at least one physical health consultation, 29.1% at least one mental health consultation and 27.4% at least one in both categories. An injury was the most frequently registered physical health consultation (40.2%), followed by performance improvement (9.8%) and stress (9.6%). Voice students registered relatively most health consultations. As far as we know, this is the first cross-sectional study using Electronic Health Record data from a PAHC to gain insight into both physical and mental health related issues in a population of classical music students. Looking at the variety of health consultations registered in the database, a multidisciplinary team and multidisciplinary approach are necessary to meet the needs of the students in terms of physical and mental health support and performance improvement.